Saxifraga aizoides Linnaeus 1753 ... - Jarvis, Charlie (Linnaean Society of London in association with the Natural History Museum, 2007)
Saxifraga aizoides Linnaeus, Species Plantarum 1: 403. 1753. "Habitat in Alpibus Lapponicis, Styriacis, Westmorlandicis, Baldis." RCN: 3159. Lectotype (Webb in Bot. J. Linn. Soc. 95: 264. 1987): Herb. Burser XVI(l): 74 (UPS). Current name: Saxifraga aizoides L. (Saxifragaceae). ... : Published as part of Jarvis, Charlie, 2007, Chapter 7: Linnaean Plant Names and their Types (part S), pp. 806-877 in Order out of Chaos. Linnaean Plant Types and their Types, London :Linnaean Society of London in association with the Natural History Museum on page 820, DOI: 10.5281/zenodo.291971 ...